Potential habitat areas and priority protected areas of Tilia amurensis Rupr in China under the context of climate change - Zhang, Fen-Guo; Zhang, Sanqing; Wu, Kefan; Zhao, Ruxia; Zhao, Guanghua; Wang, Yongji (Frontiers in Plant Science, 2024)
Tilia amurensis Rupr is one of the endangered species in China and one of the national class II keys protected wild plants, which sets ornamental, material, economic, edible, medicinal and other values in one. At present, the resources of T. amurensis are decreasing, and the prediction of the distribution of its potential habitat in China can provide a theoretical basis for the cultivation and rational management of this species. In this study, based on the collected distribution data and 38 environmental variables, we applied the MaxEnt model to predict the changes in the potential habitat of T. amurensis in China under the current and future climate scenarios, comprehensively analysed the main environmental factors affecting the distribution of this species and its suitable range, and applied the Maxran model to plan the priority protected areas for this species. The results showed that Bio18, Slope, Elev, Bio1, Bio9 and Bio2 were the dominant environmental factors affecting the distribution of T. amurensis; the area of suitable habitat for T. amurensis under the current climatic scenarios accounting for 14.7% of the total area of China, and it was mainly distributed in North China, Northeast China and part of western China; under the future climatic scenarios, the potential suitable area for T. amurensis will be mainly distributed in the Northeast China, and the total suitable area was reduced to different degrees compared with the current period, and the habitat suitability of T. amurensis was reduced, and the general trend of the centroid of suitable habitat was towards higher latitudes; the SPF value of the best plan obtained from the priority conservation area planning was 1.1, and the BLM value was 127,616, and the area of the priority conservation area was about 57.61×104 km2. The results showed that climate, soil and terrain factors jointly affect the potential geographical distribution of T. amurensis with climate and terrain factors having greater weights. The total suitable area and habitat suitability of T. amurensis in China under different climate scenarios in the future are lower than in the current period, so more effective protection should be actively adopted.